The Supercritical Fluid Extraction of Alkaloids from Papaya (Carica papaya L. var. Eksotika) Leaves - Mohamad Bukhari, Mohamad Fhaizal; Abdul Rahman, Noorsaadah; Khalid, Norzulaani; Rashid, Ahmad Hazri; Mohd Diah, Mazita (Borneo Journal of Resource Science and Technology, 2016)
Since the isolation procedures are easy, many of the earliest pure compounds isolated with biological activity were alkaloids. The nitrogen molecules in plant cells generally make the compound alkaline which make alkaloids exist in a salt form in plants. Thus, alkaloids are often extracted with water and/or acid solution system and then recovered as crystalline material by treatment using a base. The alkaloid carpaine was extracted from various part of Carica papaya L. var. Eksotika from field grown samples namely leaves, petiole and fruit peel, and from in vitro samples namely leaves, petiole, suspension cells and suspension liquid with only one artifact of impurity detected i.e. dehydrocarpaine II. Supercritical fluid extraction was analysed to obtain pure and high yield of carpaine compound as compared to conventional acid base extraction method. The ratio of ethanol/water/acetic acid used at 94.5:5:0.5 (v/v/v) was confirmed to be a better solvent system for carpaine extraction since only one pseudocarpaine i.e. dehydrocarpaine II was extracted together with carpaine. In this study, the application of single fluid of carbon dioxide in supercritical fluid extraction procedure generated pure and higher yield of carpaine compound. Additional centrifugation step should have contributed to a higher purity of the extracted carpaine.